PENGARUH PEMBELAJARAN BERDIFERENSIASI DALAM MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDI BARAI 2 - Roswita Lioba Nahak; Selfiana T.M Ndapa Lawa (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
Abstract This study aims to describe the influence of differentiated learning in the project-based learning model on the critical thinking abilities of the fourth-grade students at SDI Barai 2. This research method employs a quasi-experimental approach. The population of this study consists of all 30 students of the fourth grade at SDI Barai 2. The sampling technique used is saturated sampling. Therefore, the sample consists of 30 students. Data collection techniques involve using a test, that is, test questions becoming the research instrument. The hypothesis analysis requirements consist of tests for data normality and homogeneity, and the data analysis technique employs the t-test. The results of the normality test show that the post-test scores for both the control class and the experimental class are normally distributed, with a significance value of 0.097 > 0.05 for the experiment class and 0.148 > 0.05 for the control class. Meanwhile, the homogeneity test results show that the probability value of 0.703 > 0.05 indicates that both groups have homogeneous variances. Furthermore, the results of the average difference test between the post-test scores of the control class and the experimental class indicate that the average post-test critical thinking abilities of students in the experiment class are higher than that of the control class, namely 78.87 > 65.40. The independent t-test result is also significant, with 0.001 < 0.005. Accordingly, in conclusion, differentiated learning in the project-based learning model influences the critical thinking abilities of the fourth-grade students at SDI Barai 2. Keywords: differentiated learning; project-based learning model; students' critical thinking abilities Abstrak Tujuan dari penelitian ini untuk mendeskripsikan pengaruh pembelajaran berdiferensiasi dalam model project based learning terhadap kemampuan berpikir kritis siswa Kelas IV SDI Barai 2. Metode penelitian ini menggunakan kuasi eksperimen dengan populasi adalah seluruh siswa kelas IV SDI Barai 2 yang berjumlah 30 siswa. Teknik pengambilan sampel yang digunakan adalah sampling jenuh, sehingga jumlah sampel sebesar 30 siswa. Teknik Pengumpulan data mengunakan tes dengan instrumen penelitian soal tes. Uji persyaratan analisis hipotesis terdiri dari uji normalitas dan homogenitas data dan teknik analisis data menggunakan uji t-test. Hasil uji mormalitas data menunjukkan bahwa nilai postets kelas kontrol dan eksperiemen berdistribusi normal dengan nilai sig kelas eksperimen 0, 097 > 0,05 dan kelas kontrol 0,148 >0,05. Sementara itu, hasil uji homogenitas menunjukkan bahwa nilai probabilitas sebesar 0,703 > 0,05, maka kedua kelas mempunyai varians yang homogen. Selanjutnya hasil uji perbedaan rata-rata nilai posttest kelas kontrol dan kelas eksperimen menunjukkan bahwa rata-rata postets kemampuan berpikir kritis siswa di kelas eksperimen lebih tinggi dibandingkan dengan kelas kontrol yakni 78,87>65,40 dan hasil uji independent t-tes juga menunjukkan hasil 0,001<0,005. Dengan demikian dapat disimpulkan bahwa terdapat terdapat pengaruh pembelajaran berdiferensiasi dalam model project based learning terhadap kemampuan berpikir kritis siswa Kelas IV SDI Barai 2.